EXHIBIT F - LINNENBERGER,OJ (Tufts Archival Research Center, 2007)
Letter from the Deputy City Manager James Linenberger to Leo C. Middendorf, the labor relations representative to the San Mateo Fire Department. Responds to the accusation that the fire fighters union needed to be conferred with prior to implementing a clause in the contract of new fire fighters requiring them at the date of hire to have been smoke free for at least a year.